Preservice biology teachers’ knowledge and usage level regarding lab equipment and materials - Ahmet Gökmen; Burak Gürkan; Hikmet Türk Katırcıoğlu (Journal of Education and Learning (EduLearn), 2021)
Laboratories are an indispensable part of the fundamental sciences. Laboratories are important learning environments that enable students to relate events to daily life as well as being places where theoretical knowledge is implemented. The present study investigated the knowledge and usage level of preservice biology teachers regarding lab equipment and materials. The study utilized a descriptive survey. A total of 61 preservice biology teachers from the Biology Education Department of a public university in Turkey constituted the participants. Lab Equipment and Materials Recognition Form that is developed by the researcher of the present study was used to collect data. In the design of this form, the 9–12 grade biology curriculum was first analyzed, and a list of frequently-used equipment and materials of biology laboratories was created in line with the opinions of field experts. The form included 40 laboratories equipment and materials and questions regarding the recognition of these items, their functions, and their application processes. The preservice teachers’ answers to these questions were graded as: zero points for each incorrect answer, one point for each partially correct answer, and two points for each correct answer. The data obtained were analyzed using cluster analysis, descriptive analysis, one-way analysis of variance, and independent samples T-test in SPSS27 software, and the Polycoric correlation coefficient in Factor Analysis software. The results revealed that the preservice teachers mainly recognize the biology laboratories equipment and materials but generally lack information regarding the application process of laboratories equipment and materials.